Effect of Dietary Supplementation of Ashwagandha Root Powder on Production Performance, Egg Quality and Blood Biochemical Constituents of Laying Hens - Kumar, Sandeep (Indian Journal of Animal Nutrition, 2021)
Due to the emergence of the problem of anti-microbial resistance, the antibiotic growth promoters (AGP) are being replaced with alternatives like herbal growth promoters in poultry diets. The present study was undertaken to evaluate the effectiveness of dietary Ashwagandha root powder supplementation on egg production performance, egg quality and serum biochemical constituents in laying hens. A total of 120 laying hens (White leghorn, 22-week-old) were randomly allocated into five groups (T1, T2, T3, T4 and T5) of 24 hens with four replications having six birds in each replication. A maize - soybean meal based laying hen basal diet having all the nutrients in required quantity as per BIS, 2007 specifications was prepared that was supplemented with antibiotic was prepared and fed to experimental laying hens of control group (T1), while the treatment groups T2, T3, T4 and T5 were fed the basal antibiotic free ration supplemented with 0.25, 0.5, 0.75 and 1.0 per cent Ashwagandha root powder, respectively. Each of such diets was offered as mash ad libitum to laying hens for a period of 16 weeks (22-38 weeks of age). The findings of the study revealed that hen day egg percent and egg mass production increased significant (P<0.05) as the level of Ashwagandha root powder inclusion increased. The egg weight and internal egg parameters viz. albumen index, yolk index and Haugh unit were not affected by supplementing different levels of Ashwagandha root powder. Egg yolk total cholesterol and low density lipoprotein bound cholesterol decreased significantly (P<0.05), while high density lipoprotein bound cholesterol increased significantly (P<0.05) as level of Ashwagandha root powder inclusion increased. The results of the study showed that supplementation of 1% Ashwagandha root powder significantly (P<0.05) decreased the serum cholesterol, triglycerides and low-density lipoproteins, while significantly (P<0.05) increased the high-density lipoprotein in laying hen as compared to control birds. Internal egg quality parameters were not affected by inclusion of Ashwagandha root powder in the diet. It was concluded that inclusion of Ashwagandha root powder at 1% in the laying hen diet as a replace of antibiotic growth promoter not only improve egg production but also decreased the amount of bad cholesterol being deposited into egg.